Estudo dos flebotomíneos (Diptera: Psychodidae: Phlebotominae), em cavernas calcárias, Pains, Minas Gerais - Melo, Leandro Rocha (2021)
Phlebotomines are insects present in a wide variety of environments and are often associated with caves, where they can be found in high diversity and abundance, in addition to being a place that allows the discovery of new species due to the unique environmental characteristics present in cavities. In relation to the city of Pains, it has more than 1549 registered caves, representing with the municipality of Arcos and Doresópolis the largest concentration of limestone caves in Latin America. The municipality has calcination as its main economic activity, being known as a limestone capital of the world. Activities like this put several caves at constant risk in relation to their preservation and, consequently, of all the fauna of organisms present in this ecosystem. Being as promised of about 10% of the species of sandflies, of importance in public health, for performing the hematophagy and during the blood meal being able to become infected and later transmit the virus (phlebovirus and vesiculovirus), bacteria (Bartonella bacilliformis) and parasites, like the protozoa of the Leishmania genus. This study aims to study sandfly fauna in four limestone caves in the Pains. For this, monthly collections were carried out in 4 caves, with 3 collection points in each cave, in different photic areas, with no interior of the cave in an aphotic zone, at its entrance and close to the entrance of the cavity outside it, in a total of 12 capture points, from October 2020 to March 2021, using HP light traps, for 3 consecutive days. A total of 1402 sandflies, 963 females (68.7%) and 439 males (31.3%) were collected, up to the species level 1146 specimens (81.7%), following the classification system proposed by Galati (2003). The most abundant were Ev.edwardsi (64.6%), Mi. quinquefer (10.9%) and Ev. cortelezzii (6.6%), in a total of 22 species collected from 8 different genera. The study of sandfly fauna and its ecological characteristics can contribute to a better understanding of the different species and their relationship with the cave environment.